2022
DOI: 10.3899/jrheum.220213
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra for the Treatment of Antisynthetase Syndrome: A Monocentric Case Series and a Systematic Literature Review

Abstract: Antisynthetase syndrome (AS) is a rare autoimmune disorder whose treatment remains a challenge.1 In refractory cases, treatment escalation from glucocorticoids (GCs) and immunosuppressants to rituximab (RTX) is recommended.1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Of note, in our cohort, two patients were fully responsive to the IL-1 blocking agent anakinra. Consistently, the efficacy of anakinra in treating both patients with refractory ASS and those with different types of myocarditis has been recently reported [ 31–35 ]. This evidence may indicate a possible pathogenic role of IL-1–mediated inflammation in ASS with myocarditis.…”
Section: Discussionmentioning
confidence: 60%
“…Of note, in our cohort, two patients were fully responsive to the IL-1 blocking agent anakinra. Consistently, the efficacy of anakinra in treating both patients with refractory ASS and those with different types of myocarditis has been recently reported [ 31–35 ]. This evidence may indicate a possible pathogenic role of IL-1–mediated inflammation in ASS with myocarditis.…”
Section: Discussionmentioning
confidence: 60%
“…A systematic literature review and case series demonstrated a beneficial role of IL-1 inhibition with anakinra in seven patients with difficult to treat manifestations of ASyS, despite the use of other immunosuppressive agents [134]. Similarly, IL-6 blockade with tocilizumab in two patients with treatment-refractory ASyS-ILD showed an improvement in and stabilization of lung function over time [135].…”
Section: Other Biological Agentsmentioning
confidence: 98%